Effects and interactions of the agricultural waste residues and binder type on physical properties and calorific values of carbonized briquettes - Lubwama, Michael; Yiga, Vianney Andrew; Nalubega Lubwama, Harriet (Water, 2022)
Multiple factors are responsible for the properties of developed briquettes. The effect of the agricultural residue type in determining resulting properties of developed briquettes is seldom elucidated. Agricultural residue biochars from groundnut shells, sugarcane bagasse, coffee husks, and rice husks were used in developing carbonized briquettes using the low-cost compression method. In this study, a general factorial multi-level categorical experimental design method was used to investigate the effects and interactions of the carbonized agricultural type, binder type, and binder amount on physical properties and calorific values of developed briquettes. Statistically significant models (p < 0.05) were obtained for physical property responses of fixed carbon, ash content, volatile matter, and moisture content as well as calorific values for the developed briquettes. In experiments where only cassava starch binder (30 g and 50 g) was used, carbonized agricultural residues played a significant role in the resulting physical property. Increasing the cassava starch binder from 30 to 50 g had a minimal impact on the resulting briquette physical property. In experiments where cassava starch binder and wheat starch binder were used, it was clear that the physical property of the developed briquette was affected significantly by the carbonized agricultural residue used and binder type. Calorific values of groundnut shell and bagasse briquettes were observed to be significantly affected by the agricultural residue type. The highest calorific values of 23.9 MJ/kg and 23.3 MJ/kg were obtained for groundnut shell and bagasse biochar briquettes, respectively, when only 30 g of cassava starch binder was used. Changes in cassava and wheat starch binder amounts did not significantly affect heating values of developed groundnut shell and bagasse briquettes.
Keywords: Agricultural waste residues; Binder type; Carbonized briquettes